EVALUATION OF THE DEGREE OF ASSOCIATTION OF RECONGNISABLE BREAST CANCER RISK FACTORS AMONGST NIGERIA BREAST CANCER POPULATION - I. Obama, Y.; A. Nwanjan, N. (Scientific Journal of Medical Science, 2013)
Patientwith breast disease make up to 10% all surgical attendances and has become thecommonest group of female cancer occurring in pre-menopausal women in Nigeria.This study was conducted to ascertain the degree of association of recognizablebreast cancer risk among Nigeria breast cancer population and possible predict the strength of the riskfactors .Among risk factors considered, oral contraceptive use, age, Medicalhistory, marital status, menarche, and parity showed a strong association (X²6.197, P- 0.013 OR 1.288, X² 27.34, X² 9.062, P- 0.028, X² 21.72, P- 0.00, X²21.92, P – 0.00, OR 1.316, X² 21.147, P– 0.00) respectively thou not statistically significant at p->0.05.Thisstudy shows oral contraceptives use , and menarche has a1.3, and 1.15 forreligion time risk of developing breast cancer among Nigeria subjects. Weconclude that risk factors should be considered among Nigeria breast cancerpopulation.